2018
DOI: 10.3847/1538-4357/aa9bde
|View full text |Cite
|
Sign up to set email alerts
|

SDSS-IV MaNGA: Uncovering the Angular Momentum Content of Central and Satellite Early-type Galaxies

Abstract: We study 379 central and 159 satellite early-type galaxies with two-dimensional kinematics from the integral-field survey Mapping Nearby Galaxies at APO (MaNGA) to determine how their angular momentum content depends on stellar and halo mass. Using the Yang et al. group catalog, we identify central and satellite galaxies in groups with halo masses in the range . As in previous work, we see a sharp dependence on stellar mass, in the sense that ∼70% of galaxies with stellar mass * > - M h M 10 11 2 tend to have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 93 publications
6
45
1
Order By: Relevance
“…This is consistent with the uncertainty quoted by van de Sande et al (2017b) in which it was proposed from repeat SAMI observations that adverse seeing conditions could lower measurements of λ R by 0.05 − 0.1; our study shows that this bias could be slightly larger for very disky galaxies. Similarly, we agree with the work of Greene et al (2018) in which two corrections were suggested based on the spin parameter measured. Fig.…”
Section: Spatial Blurringsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the uncertainty quoted by van de Sande et al (2017b) in which it was proposed from repeat SAMI observations that adverse seeing conditions could lower measurements of λ R by 0.05 − 0.1; our study shows that this bias could be slightly larger for very disky galaxies. Similarly, we agree with the work of Greene et al (2018) in which two corrections were suggested based on the spin parameter measured. Fig.…”
Section: Spatial Blurringsupporting
confidence: 92%
“…Previous studies have sought to quantify or correct this bias (e.g. D 'Eugenio et al 2013;van de Sande et al 2017a,b;Greene et al 2018;Graham et al 2018), and we investigate how well such corrections perform. In particular, we focus on the recent work Graham et al (2018), who used Jeans Anisotropic Modelling (JAM) to derive a general analytic correction to λ R for regularly rotating galaxies of different types, based on the ratio of the width of the point spread function (σ PSF ) to the effective radius of the galaxy (R eff ); we investigate how well it performs when applied to 3D dynamical galaxy models.…”
Section: Introductionmentioning
confidence: 97%
“…In the two right-most panels, we show the running average rotational support for each overdensity bin, with a slight offset from the center of the bin for clarity. As shown in Bezanson et al (2018b), the average range in rotational support tends to decrease with increasing stellar mass, which is consistent with studies of massive, quiescent galaxies in the local Universe (Veale et al 2017;Greene et al 2018). We do not see a strong environmental trend at all masses, but we note two statistically significant trends at the massive end of the sample.…”
Section: Nearby Quiescent Galaxies From the Massive And Atlas 3d Surveyssupporting
confidence: 87%
“…From Figure 5a, it is clear that the number density of FRs overwhelms SRs for most stellar masses covered by SAMI, with SRs matching the fraction of FRs only at > 2 × 10 11 M (see also Khochfar et al 2011;Emsellem et al 2011;Greene et al 2017Greene et al , 2018van de Sande et al 2017b;Brough et al 2017). We should note that this transition mass looks systematically lower than that found in Graham et al (2018, Figure 13) based on MaNGA galaxies.…”
Section: Al 2007)mentioning
confidence: 66%